the graph of y=- square root x=7 can be obtained from the graph of y=square root x b shifting horizontally

_?_ units to the _?_ and reflecting across the _?_ -axis.

he graph of y=- square root x=7 can be obtained from the graph of y=square root x b shifting horizontally

7 units to the left and reflecting across the x -axis.

Will it be the same answer if it is y=- square root x+7 instead of x=7

yes it will.

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up